Clinical Assessment and Cytomorphometric Analysis of Buccal Mucosal Cells in Behçet’s Disease Patients - Mohammed, Dalya; Yas , Layla S (Journal of Baghdad College of Dentistry, 2019)
Background: Behçet’s disease (BD) is a disorder of systemic inflammatory condition. Its important features are represented by recurrent oral, genital ulcerations and eye lesions. Aims. The purpose of the current study was to evaluate and compare cytological changes using morphometric analysis of the exfoliated buccal mucosal cells in Behçet’s disease patients and healthy controls, and to evaluate the clinical characteristics of Behçet’s disease. Methods. Twenty five Behçet’s disease patients have been compared to 25 healthy volunteers as a control group. Papanicolaou stain was used for staining the smears taken from buccal epithelial cells to be analyzed cytomorphometrically. The image analysis software has been used to evaluate cytoplasmic, nuclear areas and the nuclear/cytoplasmic ratio (N/C). Results. The cytoplasmic and nuclear area of buccal cells of Behçet’s disease cases were significantly smaller than those of healthy volunteers. However, the N/C ratio remained the same when compared between both groups. All patients had recurrent oral ulcer and none of the patient had cardiac and pulmonary symptoms. Conclusion. Cytomorphometric analysis and exfoliative cytology techniques have the ability to detect the alterations in buccal epithelial cells caused by Behçet’s disease.